Hacia un marco analítico explicativo de las políticas de los estados de la Unión Americana respecto a la inmigración indocumentada - Torre Cantalapiedra, Eduardo (El Colegio de México A.C., 2015)
In the middle of the first decade of the twenty-first century, policies proliferated throughout the United States regarding un documented immigrants, including laws and other measures that generally sought to place restrictions on them. The aim of this paper is to develop the groundwork for an analytical frame work to explain the existence and restrictive nature of these policies. It is divided into three parts: firstly, the historical and political context of state policies against undocumented immigrants is briefly explained. Secondly, the factors underlying citizens’ support for these policies are set out. Finally, the motives for state political leaders to promote and approve them are explained.